Redefining rurality: cosmopolitanism, whiteness, and the New Latino Diaspora. Issue 3 (4th May 2017) - Sierk, Jessica
ABSTRACT: In mainstream discourse, rural generally implies white, while urban signifies not-white. However, what happens when 'rural' communities experience demographic change? This paper examines how students from a rural, New Latino Diaspora community in a Midwestern state complicate traditional notions of rurality. Data from participant observations and ethnographic interviews indicate that students from this near-majority-Latino community do not view it as rural even though its population is under 2500. Students allude to an alternative youth subculture influenced by incoming Latino students from cities in Mexico, Guatemala, and California. They contrast this with the more stereotypical subcultures they observe in neighboring, rural, majority-white communities. Demographically transitioning, rural schools present unique contexts for students to not only encounter their own privilege, but also to learn how to leverage that privilege to further the aims of social justice. However, this will not occur without explicit and careful planning, implementation, reflection, and teacher training.